Erikson’s Psychosocial Development Studies on Merida in the Brave Movie: Studi Perkembangan Psikososial Erikson tentang Merida dalam Film Brave - Anjeliani; Muhajir, Fatimah (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2025)
This research aims to determine how the stages of Merida’s psychosocial development are represented in the Brave movie. This research uses qualitative research as the method and psychosocial development theory by Erik Erikson as the approach. Based on the result of this research, the researcher found that Merida passes five stages of the eight stages of psychosocial development theory, namely: 1) Trust vs. Mistrust is evident as Merida develops a sense of trust and feels comfortable with her mother, 2) Autonomy vs. Shame is evident as Merida develops a sense of independence through playing archery, 3) Initiative vs. Guilt is evident as Merida takes the initiative to pick up her arrow that is off target without asking her parents to accompany her, 4) Industry vs. Inferiority is evident as Merida gains skills through homeschooling with her mother, and 5) Identity vs. Role Confusion is evident as Merida knows her identity and can voice it. In conclusion, Merida is portrayed as a character who undergoes development across various stages of Erik Erikson's psychosocial theory. Her journey from building trust and autonomy to taking initiative, gaining industry skills, and ultimately establishing her identity reflects a complex portrayal of psychosocial growth in the Brave movie.